CHARACTERISTICS OF FORMATION AND DEVELOPMENT OF THE ART OF BATHROOMING - Khatamova Durdona Madaminovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article examines the grouping of rooms in Central Asian bathrooms according to size and design, constructive solutions and functions, the basic methods and general rules in the form of public baths. The peculiarities of the formation and development of the art of bathing are studied. A brief history of the baths, one of the ancient architectural monuments, the construction process, architectural solutions, some healing properties are also covered. Long-term scientific research has been carried out on the basis of repeated visits and examinations of these monuments, as well as scientific sources of scientists in the field.